High-Quality de Novo Genome Assembly of the Dekkera bruxellensis Yeast Using Nanopore MinION Sequencing. Issue 10 (1st October 2017) - Fournier, Téo; Gounot, Jean-Sébastien; Freel, Kelle; Cruaud, Corinne; Lemainque, Arnaud; Aury, Jean-Marc; Wincker, Patrick; Schacherer, Joseph; Friedrich, Anne
Abstract: Genetic variation in natural populations represents the raw material for phenotypic diversity. Species-wide characterization of genetic variants is crucial to have a deeper insight into the genotype-phenotype relationship. With the advent of new sequencing strategies and more recently the release of long-read sequencing platforms, it is now possible to explore the genetic diversity of any nonmodel organisms, representing a fundamental resource for biological research. In the frame of population genomic surveys, a first step is to obtain the complete sequence and high-quality assembly of a reference genome. Here, we sequenced and assembled a reference genome of the nonconventional Dekkera bruxellensis yeast. While this species is a major cause of wine spoilage, it paradoxically contributes to the specific flavor profile of some Belgium beers. In addition, an extreme karyotype variability is observed across natural isolates, highlighting that D. bruxellensis genome is very dynamic. The whole genome of the D. bruxellensis UMY321 isolate was sequenced using a combination of Nanopore long-read and Illumina short-read sequencing data. We generated the most complete and contiguous de novo assembly of D. bruxellensis to date and obtained a first glimpse into the genomic variability within this species by comparing the sequences of several isolates. This genome sequence is therefore of high value for population genomic surveys and represents a reference to study genome dynamic in this yeast species.